2017
DOI: 10.3390/sports5030053
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Utilisation of Stand up Paddle Boarding in Australia

Abstract: Stand Up Paddle Boarding (SUP) has grown exponentially in the last few years with unprecedented participation rates globally. Despite some scientific research on physiological and performance variables, minimal information exists regarding participation and utilisation. The purpose of this study was to discover more about how and where people participate in the relatively new sport of SUP. An open-source online survey application was administered internationally to active SUP participants to capture informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 16 publications
1
11
0
1
Order By: Relevance
“…Thus, although of lower agreement with OBLA, this methodological approach increases the applicability of CV in training routines. Furthermore, this study used efforts between 400 and 800 m, which are uncommon in SUP competitions (21), and this could be a limitation of our results. Thus, future studies should test the relations with OBLA, using longer efforts to determine CV in SUP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, although of lower agreement with OBLA, this methodological approach increases the applicability of CV in training routines. Furthermore, this study used efforts between 400 and 800 m, which are uncommon in SUP competitions (21), and this could be a limitation of our results. Thus, future studies should test the relations with OBLA, using longer efforts to determine CV in SUP.…”
Section: Discussionmentioning
confidence: 99%
“…Eight athletes (age: 23 6 3 years (range: 18-27 years); height: 173.0 6 9.0 cm; body mass: 66.9 6 5.8 Kg; body fat: 9.4 6 1.9%) participated in this study, with a minimum of 2 years of competitive SUP experience, training 5 times per week, with a mean volume higher than 10 h•wk 21 . The study was approved by the Ethics Committee of the Federal University of Alagoas, Brazil, on the protocol number 58508116.1.0000.5013.…”
Section: Subjectsmentioning
confidence: 99%
“…On the one hand, Azevedo, Carvalho, Batista & Columá (2017) aim to discuss, via a review, the relationship of SUP practice as an adventure sport, concluding that this form of adventure has become a growing practice, especially in coastal regions. On the other, Schram and Furness (2017c) conducted a study via an on-line questionnaire, with the aim of finding out more about how and where people practise SUP. They concluded that participants most commonly used SUP for fun and fitness for around 3 hours a week, predominantly at the beach with friends, with around half of respondents reporting competitive participation.…”
Section: Other Issuesmentioning
confidence: 99%
“…These studies stated that SUP is a globally performed physical activity but with a high concentration in Australia (6). In addition, it proposed that SUP athletes possess a high level of fitness, strength and balance (3) and that long term participation appeared to be associated with improvements in body composition, aerobic fitness and trunk muscle endurance (4).…”
Section: Introductionmentioning
confidence: 99%